Hubungan Hukum Keluarga Islam dengan Isu Hak Anak dan Pencatatan Perkawinan di Malaysia - Tubagus Farhan Maulana (Syakhsiyah Jurnal Hukum Keluarga Islam, 2025)
This study investigates the interplay between Islamic family law, children's rights, and marriage registration in Malaysia. As a Muslim-majority country, Malaysia's Islamic family law—primarily based on the Shafi'i school—has developed under the dual influences of British colonial legacy and legal modernization. The research traces the historical evolution of Islamic family law, highlighting the roles of local customs, legal codification, and its integration with the Common Law system. Although marriage registration is legally required, the validity of marriage is determined by Islamic principles rather than state procedures. Children's rights, governed by the Child Act 2001, encompass issues of custody, maintenance, and protection from abuse. Institutions such as the Family Support Division play a pivotal role in enforcing court-ordered support for children and ex-wives. The findings reveal that despite ongoing reforms, tensions persist in aligning Islamic family law with Malaysia's broader legal framework. A balanced approach that harmonizes Islamic values with contemporary legal standards is essential for safeguarding children's rights and ensuring effective marriage governance, positioning Islamic family law as a dynamic and responsive legal instrument.